Sustainable development in Peru and the commission of environment and ecology - Morales Castillo, Fabiola (2002)
In this work I will present the concept of sustainable development and the guidelines that must be followed to achieve it, the functions of the State, the legislative function of the Congress of the Republic as well as the functions of the Work Commissions. In addition to exposing the main objectives, activities and roles according to the work plan for the 2002-2003 period of the Environment and Ecology Commission. Finally, with the topic of legislation as a tool to promote the rational and sustainable use of natural resources within the framework of Peru's environmental strategy. Sustainable development is a concept that has been developing in recent decades. It implies the integrated management of natural resources through the application of efficient policies that allow a balance between development and conservation taking into account the needs of present and future generations.